<span>4x^2 + 24x + 32 = 4(x^2 + 6x + 8)
6/2 = 3 so:
= 4( (x+3)^2 - 3^2 + 8 )
= 4( (x+3)^2 - 9 + 8)
= 4( (x+3)^2 - 1)
= 4(x+3)^2 - 4
vertex will be the minimum point, so: now,
4(x+3)^2 - 4 is at a minimum when x = -3 because it makes the stuff being squared equal to 0 so we know the x cord of vertex
is -3 the y cord is the constant on the end, -4
Hope this helps</span>
Nobody can really answer this question because we don’t know what what your supposed to be writing a response to
Answer:
I will go to church and thank God
Explanation:
After I will Relax my body
Answer:
THEY HAVE NOT PASSED THE TEST..
Answer:
I can't see the picture? Do you have a less blurrier one??
Explanation: